Seismic Drift Control and Building Periods - Teal, Edward J. (Engineering Journal, 1978)
General parameters of seismic drift control were discussed by the author in a 1975 article titled "Seismic Drift Control Criteria" in the AISC Engineering Journal. However, the confusion which still exists concerning building periods and drift control, particularly in relation to code seismic design, indicates that these subjects deserve more attention. Building period governs the behavior of structures when they are subjected to earthquake ground motions, even when the dynamic response of the structure is forced far into the inelastic range during some of the strong motion. Drift, or distortion, really governs the performance of a building in terms of damage both to the structural frame and to nonframe elements. The designer needs to have a good understanding of the factors affecting these subjects. Knowing the limiting parameters is therefore important.